A NEW TECHNOLOGY CULTURAL LANDSCAPE HERITAGE - Syukur Iman Jaya Gulo; Ramadhani Fitri; Bhakti Alamsyah (INFOKUM, 2022)
Nias Island is one of the islands in North Sumatra which has various potentials in the form of tourism. One of the tours in Nias is the Nias Heritage Museum. The Nias Heritage Museum not only collects, protects and maintains Nias cultural heritage objects, but also conducts research. The Nias Heritage Museum has many places, namely exhibition venues, cafes, mini zoos, inns, meeting rooms, recreation parks and libraries. This research uses the method of identifying green open spaces and public spaces in the Nias museum as the Cultural Landscape of Nias. For now, there are three places that are used as public spaces, while green open spaces are in the middle of the museum. To protect every culture that exists in Nias and become a source of knowledge for the people of Nias and the people of Indonesia,